APPLICATION FOR CONTROL OF DISTANCE LIGHTS USING MICROCONTROLLER NODEMCU ESP 8266 BASED ON INTERNET OF THINGS (IOT) - Sahtyawan, Rama; Wicaksono, Arief Ikhwan (Sekolah Tinggi Teknologi Adisutjipto Yogyakarta, 2020)
Control systems in the field of technology, electronic devices must be controlled. But there are still those who oppose if the room does not have a place anywhere, where there is no one at home, other people forget to change the lights, it is very inconvenient if you have to go home, even though if the lights are left activated there will be a waste, from which It was stated that a light monitoring device was provided using the Internet-based (IoT) tea-based Relay module using the NodeMcu ESP 8266 microcontroller which has been equipped with a wifi module, so that the led lights can be monitored by the user in realtime so using the IoT Program platform using the Blynk application, which can be controlled via handphone, In the system implementation, a display is made using Blynk. There are 4 on and off switch buttons which are used to facilitate and activate the Led lights. In this research, the control of Led using blynk is done 10 times. Led control testing is used to see each procedural function running correctly as expected, the results of tests that have been done get the results of 10x experiments that have been done to get 2 x interrupted experiments in the LEDs needed to connect the wifi network